Effects of Reversal Technique for Neuromuscular Paralysis on Time to Recovery of Bowel Function after Craniotomy. Issue 5 (May 2023) - Deljou, Atousa; Soleimani, Jalal; Sprung, Juraj; Schroeder, Darrell R; Weingarten, Toby N.
Background: Non-depolarizing neuromuscular blockade can be reversed with neostigmine/glycopyrrolate or sugammadex. We test the hypothesis that sugammadex is associated with earlier postoperative recovery of bowel function (first bowel movement, BM). Methods: In adult patients undergoing craniotomy from 2016 to 2019, we identified time of first postoperative BM after receiving neostigmine/glycopyrrolate or sugammadex to reverse neuromuscular blockade. Logistic and proportional hazard regression, with and without inverse probability of treatment weighting (IPTW), were used to assess whether sugammadex is associated with earlier recovery of bowel function. Results: Seven hundred and thirty-one patients underwent craniotomy, 323 (44.2%) received neostigmine/glycopyrrolate, and 408 (55.8%) sugammadex. From logistic regression analysis, the proportion of patients having a BM within the first 24 and 48 hours was higher in sugammadex group (unadjusted OR [95% CI]) 1.79 [1.16 to 2.77] P = .009; and 1.45 [1.08 to 1.94] P = .014; IPTW adjusted OR [95% CI]) 1.58 [.95, 2.61] P = .078; and 1.38 [.95 to 2.02] P = .095 for 24 and 48 h, respectively). From proportional hazards regression, sugammadex was associated with improved bowel function recovery (unadjusted hazard ratio (HR) [95% CI] 1.35 [1.08, 1.68], P = .008; IPTW adjusted HR 1.29 [.97 to 1.71], P = .076). Conclusion: Patients undergoing craniotomy who had neuromuscular blockade reversed with sugammadex may have earlier recovered bowel function compared to patients reversed with neostigmine/glycopyrrolate.